PENILAIAN INDIKATOR KESEHATAN HUTAN MAMAR DESA NIUKBAUN KECAMATAN AMARASI BARAT - Lubalu, Diva Joy Diniella; Sinaga, Pamona S; Kaho, Norman P.L.B. Riwu Kaho P.L.B. Riwu; Mau, Astin E (Tengkawang : Jurnal Ilmu Kehutanan, 2025)
Mamar, as a form of local wisdom in the West Timor community known as the “Amarasi System,” provides benefits not only in economic, social, and cultural aspects but also in ecological aspects. However, challenges such as human activities, lack of understanding of sustainable management, and livestock grazing threaten the existence of Mamar, which plays a crucial ecological role in the environment. This study aims to assess the forest health status of Mamar in Niukbaun Village using the Forest Health Monitoring method across 18 cluster plots, based on four measurement indicators: vitality, productivity, biodiversity, and site quality. The results indicate that the forest health status, based on the tree damage indicator at the cluster plot level, is categorized as healthy. The crown condition indicator shows 109 trees with low Visual Crown Ratio (VCR) values and 37 trees with moderate VCR values. For the productivity indicator, the highest Basal Area (LBDS) value is 0.39 m² and the lowest is 0.05 m², while the highest volume is 2.75 m³ and the lowest is 0.39 m³. Regarding the biodiversity indicator, species diversity is classified as moderate, species richness as low to moderate, and species evenness as moderate. The site quality indicator shows soil pH ranging from acidic to neutral and organic carbon content ranging from moderate to very high. Keywords: Agroforestry, Forest Health, Forest Health Monitoring, Mamar, Niukbaun Village Abstrak Mamar sebagai kearifan lokal masyarakat Timor Barat dikenal dengan “Sistem Amarasi” memiliki manfaat tidak hanya dalam aspek ekonomi, sosial dan budaya tetapi juga aspek ekologi. Namun disamping itu, terdapat beberapa masalah seperti aktivitas manusia, kurangnya pemahaman tentang pengelolaan berkelanjutan hingga penggembalaan ternak dapat mengancam keberadaan mamar yang secara ekologi memberikan peran penting terhadap lingkungan. Tujuan penelitian ini adalah untuk mengetahui status kesehatan hutan Mamar Desa Niukbaun dengan metode Forest Health Monitoring pada 18 klaster plot melalui empat indikator pengukuran yaitu : indikator vitalitas, indikator produktivitas, indikator biodiversitas serta indikator kualitas tapak. Hasil penelitian menunjukkan bahwa status kesehatan hutan mamar melalui indikator kerusakan pohon pada tingkat klaster plot berada pada kategori sehat, status kesehatan melalui indikator kondisi tajuk terdapat 109 pohon dengan nilai VCR rendah dan 37 pohon memiliki nilai VCR yang sedang, pada indikator produktivitas memiliki nilai LBDS tertinggi 0,39 m² dan terendah 0,05 m² sedangkan nilai volume tertinggi 2,75 m³ dan terendah 0,39 m³. Pada indikator biodiversitas : tingkat keanekaragaman berada pada kategori sedang, tingkat kekayaan rendah-sedang dan tingkat kemerataan berada pada kategori sedang. Penilaian dengan indikator kualitas tapak untuk pH tanah berada pada kategori masam-netral dan C-Organik yang sedang-sangat tinggi. Kata Kunci: Agroforestri, Forest Health Monitoring, Mamar, Desa Niukbaun, Kesehatan Hutan